A sample of 6C radio sources designed to find objects at redshift > 4: III --- imaging and the radio galaxy K-z relation - Jarvis, M; Rawlings, S; Eales, S; Blundell, K; Bunker, A; Croft, S; McLure, R; Willott, C (2001)
In this paper, the third and final of a series, we present complete K-band imaging and some complementary I-band imaging of the filtered 6C* sample. We find no systematic differences between the K-z relation of 6C* radio galaxies and those from complete samples, so the near-infrared properties of luminous radio galaxies are not obviously biased by the additional 6C* radio selection criteria (steep spectral index and small angular size). The 6C* K-z data significantly improve delineation of the K-z relation for radio galaxies at high-redshift (z >2). Accounting for non-stellar contamination, and for correlations between radio luminosity and stellar mass, we find little support for previous claims that the underlying scatter in the stellar luminosity of radio galaxies increases significantly at z >2. In a particular spatially-flat universe with a cosmological constant, the most luminous radio sources appear to be associated with galaxies with a luminosity distribution with a high mean (~5 Lstar), and a low dispersion (sigma ~ 0.5 mag) which formed their stars at epochs corresponding to z >~2.5. This result is in line with recent sub-mm studies of high-redshift radio galaxies and the inferred ages of extremely red objects from faint radio samples.